2022
DOI: 10.1186/s13256-022-03326-6
|View full text |Cite
|
Sign up to set email alerts
|

Breast carcinoma metastasis to the cheek: a case report

Abstract: Background Breast carcinoma is a common tumor in women, but it rarely metastasizes to the oral region. Furthermore, metastases to the oral region occur mainly to the maxillary and mandibular bone and rarely to soft tissue. Case presentation We describe a case of breast cancer metastasis to the buccal area. Examination of the right buccal mass of a 66-year-old Japanese woman was suggestive of breast cancer metastasis, and a breast lump was detected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%
“…Metastasis can even appear in patients after a prolonged disease-free period [ 15 ]. Once the carcinoma spreads to the oral cavity, the presenting symptoms are numerous and varied, which include bleeding, swelling, loose tooth, numbness, trismus, foul-smelling breath, pathological fractures, ulceration, and lymphadenopathy [ 15 , 16 ]. A review of articles showed that numb chin syndrome (NCS) is also a sign of oral metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Breast carcinoma is a common tumor in women, but it rarely metastasizes to the oral region; furthermore, metastases to the oral region occur mainly to the maxillary and mandibular bone and rarely to soft tissue 6–8 . We report metastatic tumor of the mandible on panoramic radiography and multidetector computed tomography (MDCT), especially a case report from the breast cancer.…”
Section: Introductionmentioning
confidence: 99%